Hepatitis C treatment outcomes among people who inject drugs experiencing unstable versus stable housing: Systematic review and meta-analysis. - Sarah Kimball; Marley Reynoso; Courtney McKnight; Don Des Jarlais (PLoS ONE)
Background The prevalence of hepatitis C virus (HCV) among people who inject drugs (PWID) is between 50-70%. Prior systematic reviews demonstrated that PWID have similar direct acting antiviral treatment outcomes compared to non-PWID; however, reviews have not examined treatment outcomes by housing status. Given the links between housing and health, identifying gaps in HCV treatment can guide future interventions. Methods We conducted a systematic review using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We searched six databases for articles from 2014 onward. Two reviewers conducted title/abstract screenings, full-text review, and data extraction. We extracted effect measures for treatment initiation, adherence, completion, success, and reinfection by housing status. Studies underwent quality and certainty assessments, and we performed meta-analyses as appropriate. Results Our search yielded 473 studies, eight of which met inclusion criteria. Only the treatment initiation outcome had sufficient measures for meta-analysis. Using a random-effects model, we found those with unstable housing had 0.40 (0.26, 0.62) times the odds of initiating treatment compared to those with stable housing. Other outcomes were not amenable for meta-analysis due to a limited number of studies or differing outcome definitions. Conclusions Among PWID, unstable housing appears to be a barrier to HCV treatment initiation; however, the existing data is limited for treatment initiation and the other outcomes we examined. There is a need for more informative studies to better understand HCV treatment among those with unstable housing. Specifically, future studies should better define housing status beyond a binary, static measure to capture the nuances and complexity of housing and its subsequent impact on HCV treatment. Additionally, researchers should meaningfully consider whether the outcome(s) of interest are being accurately measured for individuals experiencing unstable housing.